2019
DOI: 10.1002/naaq.10087
|View full text |Cite
|
Sign up to set email alerts
|

Egg Production of Gulf Killifish Is Dependent on Broodstock Rearing Density but Not Spawning Substrate Surface Area

Abstract: The Gulf Killifish Fundulus grandis is a popular baitfish for recreational fisheries and is a candidate for commercial‐scale culture; however, its relatively low fecundity compared to other baitfish presents a production challenge. Egg output in relation to broodstock densities and spawning mat surface areas was evaluated in recirculating aquaculture systems (RASs). In experiment 1, broodstock were stocked at two densities (45 and 90 fish/m³), with eggs collected three times per week for 8 weeks. Broodstock (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The lack of sex effects in this study might be attributed to the age of the fish used, which were probably young-of-the-year (Greeley and MacGregor, 1983) and not reproductively active at the time of capture. In addition, fish in the current study were held at relatively high density (∼60 fish per m 3 ), which has been shown to reduce egg production in F. grandis (Chesser et al, 2019). However, over the course of laboratory maintenance, fish grew significantly and developed dimorphic coloration typical of sexually mature individuals of this species.…”
Section: Lack Of Collection Site and Sex Effects On Aerobic Metabolismmentioning
confidence: 94%
“…The lack of sex effects in this study might be attributed to the age of the fish used, which were probably young-of-the-year (Greeley and MacGregor, 1983) and not reproductively active at the time of capture. In addition, fish in the current study were held at relatively high density (∼60 fish per m 3 ), which has been shown to reduce egg production in F. grandis (Chesser et al, 2019). However, over the course of laboratory maintenance, fish grew significantly and developed dimorphic coloration typical of sexually mature individuals of this species.…”
Section: Lack Of Collection Site and Sex Effects On Aerobic Metabolismmentioning
confidence: 94%
“…The lack of sex effects in this study 568 might be attributed to the age of the fish used, which were probably young-of-the-year (Greeley 569 and McGregor, 1983) and not reproductively active at the time of capture. In addition, fish in the 570 current study were held at relatively high densities (~60 fish per m 3 ), which have been shown to 571 reduce egg production in F. grandis (Chesser et al, 2019). On the other hand, over the course of 572 laboratory maintenance, fish grew significantly and developed dimorphic coloration typical for 573 sexually mature individuals of this species.…”
Section: Differences 565mentioning
confidence: 95%
“…Premised on previous ndings that the species is a continuous substrate spawner with low fecundity (Okyere, 2012), this experiment (1) assessed the spawning potential, (2) investigated whether the killi sh has preference for the colour of its spawning substrate, (3) monitored the stages of embryonic development, and 4monitored the sizes of embryos and duration of embryonic development, in ex situ fresh-and-brackish water environments. With the growing interests in using killi sh for a multiplicity of purposes including breeding for bait sh (Chesser et al, 2019) and as tool for embryology education (Genade, 2016), the usefulness this study may possibly traverse biocontrol to other facets killi sh utility.…”
Section: Introductionmentioning
confidence: 99%